SUPERVISI PENDIDIKAN: KONSEP, MODEL, PENDEKATANDANTEKNIK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Gracia Lumbantobing; Dr. Nurmayani, M.Ag; Naomi Nathanya Libe Gracella Pakpahan; Nabila Azzahra Putri Irwansyah; Nanda Yuliana Sinaga; Theresa Intan Situmorang; Margareth Nainggolan; Lidya Pratiwi; NazzahrahAyuClara (STKIP Subang, 2026)
Quality education requires systematic management and effective learning processes, one of whichis achieved through educational supervision. This study aims to describe educational supervision, specifically: (1) the concept of educational supervision, (2) models of educational supervision, (3) approaches to educational supervision, and (4) techniques of educational supervision. The researchwas conducted using a literature review method with a qualitative descriptive approach toanalyzevarious literature related to educational supervision. The results of the discussion indicatethat educational supervision consists of two main dimensions: managerial supervision aimedat managing school administration and resources, and academic supervision aimed at assistingteachers in developing the ability to manage the learning process to achieve learning objectives. The effectiveness of educational supervision in improving the quality of learning is greatlyinfluenced by the appropriateness of the selected model, approach, and supervision techniquesused.